Correlation of the Modified Japanese Orthopedic Association With Functional and Quality-of-Life Outcomes After Surgery for Degenerative Cervical Myelopathy: A Quality Outcomes Database Study. Issue 6 (23rd December 2022) - Yee, Timothy J.; Upadhyaya, Cheerag; Coric, Domagoj; Potts, Eric A.; Bisson, Erica F.; Turner, Jay; Knightly, Jack J.; Fu, Kai-Ming; Foley, Kevin T.; Tumialan, Luis; Shaffrey, Mark E.; Bydon, Mohamad; et al.
Abstract : Abstract : BACKGROUND: The modified Japanese Orthopedic Association (mJOA) score is a widely used and validated metric for assessing severity of myelopathy. Its relationship to functional and quality-of-life outcomes after surgery has not been fully described. OBJECTIVE: To quantify the association of the mJOA with the Neck Disability Index (NDI) and EuroQol-5 Dimension (EQ-5D) after surgery for degenerative cervical myelopathy. METHODS: The cervical module of the prospectively enrolled Quality Outcomes Database was queried retrospectively for adult patients who underwent single-stage degenerative cervical myelopathy surgery. The mJOA score, NDI, and EQ-5D were assessed preoperatively and 3 and 12 months postoperatively. Improvement in mJOA was used as the independent variable in univariate and multivariable linear and logistic regression models. RESULTS: Across 14 centers, 1121 patients were identified, mean age 60.6 ± 11.8 years, and 52.5% male. Anterior-only operations were performed in 772 patients (68.9%). By univariate linear regression, improvements in mJOA were associated with improvements in NDI and EQ-5D at 3 and 12 months postoperatively (all P < .0001) and with improvements in the 10 NDI items individually. These findings were similar in multivariable regression incorporating potential confounders. The Pearson correlation coefficients for changes in mJOA with changes in NDI were −0.31 and −0.38 at 3 and 12 months postoperatively. The Pearson correlation coefficients for changes in mJOA with changes in EQ-5D were 0.29 and 0.34 at 3 and 12 months. CONCLUSION: Improvements in mJOA correlated weakly with improvements in NDI and EQ-5D, suggesting that changes in mJOA may not be a suitable proxy for functional and quality-of-life outcomes.